Capital Punishment in Ohio: Aggravating Circumstances - Hilliard, Elaine C. (1982)
The state of Ohio enacted a new death penalty statute which became effective October 19, 1981. As of January 18, 1983, eighty-three defendants had been indicted under the new statute. It is, therefore, both necessary and timely to evaluate Ohio's statutory delineation of who may die and its effect for compliance with constitutional mandates. This Note sets forth the hypotheses and supporting legal authority for analyzing Ohio's statutory aggravating circumstances individually and in the aggregate on equal protection and procedural due process grounds